THE TOURISM POTENTIAL MAPPING IN WERU SUBDRISTRICT SUKOHARJO REGENCY YEAR 2019 - Rahmawati, Talitha; Rahman, MS Khabibur; Rohsulina, Pranichayudha (Journal of Geography Science and Education, 2019)
This research aims to: 1) to understand the distribution of tourist location in Weru Sub-district Sukoharjo Regency, 2) to analyse the tourism potential in Weru Subdistrict Sukoharjo Regency. This research used spatial descriptive method by using primary data from coordinate point of each tourist location and secondary data from Indonesian Topographic Map (RBI). The data collection used in this research was documentation and observation, while the data analysing technique was scoring technique and map analysing. Scoring technique is done by using three main variables which are tourism’s attraction, accessibility, facilities and infrastructure. The research result showed that Weru Sub-district has three tourism’s attractions which consist of two cultural attractions and one natural attraction that are spread in two locations in Karanganyar Village (Sirih Temple) and Jatingarang Village (Curug Pleret and Ki Ageng Purwoto Sidiq Tomb). From the observation and the score calculation, it was shown that Curug Pleret was categorized as a very potential tourist site, while Ki Ageng Purwoto Sidiq Tomb and Sirih Temple were categorized as potential and less potential tourist location respectively.Keywords: Tourist location, tourism potential, Weru Subdistrict